Fornax A, Centaurus A, and other radio galaxies as sources of ultrahigh energy cosmic rays. (2nd June 2018) - Matthews, J H; Bell, A R; Blundell, K M; Araudo, A T
ABSTRACT: The origin of ultrahigh energy cosmic rays (UHECRs) is still unknown. It has recently been proposed that UHECR anisotropies can be attributed to starburst galaxies or active galactic nuclei. We suggest that the latter is more likely and that giant-lobed radio galaxies such as Centaurus A and Fornax A can explain the data.